2016
DOI: 10.1097/md.0000000000003216
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Low Serum Bicarbonate Levels Predict Acute Kidney Injury After Cardiac Surgery

Abstract: Acute kidney injury (AKI) after cardiac surgery is a common and serious complication. Although lower than normal serum bicarbonate levels are known to be associated with consecutive renal function deterioration in patients with chronic kidney injury, it is not well-known whether preoperative low serum bicarbonate levels are associated with the development of AKI in patients who undergo cardiac surgery. Therefore, the clinical implication of preoperative serum bicarbonate levels on AKI occurrence after cardiac … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Regarding bicarbonate, its utility in the diagnosis of AKI has already been described and subtle reduction is associated with worsening renal function 35 . Bicarbonate acts on tissue by increasing the availability of oxygen in the medullary region and reducing free radicals' formation 36 . In metabolic acidosis, ammonia production occurs in the medullary region, leading to increased inflammation and tubular injury 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Regarding bicarbonate, its utility in the diagnosis of AKI has already been described and subtle reduction is associated with worsening renal function 35 . Bicarbonate acts on tissue by increasing the availability of oxygen in the medullary region and reducing free radicals' formation 36 . In metabolic acidosis, ammonia production occurs in the medullary region, leading to increased inflammation and tubular injury 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that during recent years several studies have tried to introduce reliable markers such as cystatin C, kidney injury molecule-1 (Kim-1), neutrophil gelatinase-associated lipocalin (NGAL), etc. for early diagnosis or preventive treatment of CSA-AKI (8)(9)(10)(11), no reliable marker exists for early diagnosis of CSA-AKI, and the researchers keep working on the available markers, their accuracy and prognostic value for diagnosis of CSA-AKI (12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Jung et al . also demonstrated that patients with low serum bicarbonate levels before cardiac surgery had a higher incidence of postoperative AKI independent of other risk factors for AKI development 19 . Similarly, recent observational studies found that lower serum bicarbonate levels predicted the development of AKI 5,20 , thereby supporting a close association between serum bicarbonate level and renal dysfunction.…”
Section: Discussionmentioning
confidence: 97%